2018
DOI: 10.1111/add.14128
|View full text |Cite
|
Sign up to set email alerts
|

Direct‐acting antiviral treatment of chronic HCV‐infected patients on opioid substitution therapy: Still a concern in clinical practice?

Abstract: In Germany, direct-acting antiviral treatment of former or current drug users with or without opioid substitution therapy can achieve equally high sustained virological response rates as in patients with no history of drug use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
54
4
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 23 publications
11
54
4
5
Order By: Relevance
“…Such groups were excluded from clinical trials of DAA treatment efficacy due to strict eligibility criteria; thus, our cohort represents a real‐world PWID population treated with DAAs. We found that there was no difference in SVR by any of these characteristics, which is similar to the findings from others . However, among PWID who did not achieve SVR, there was a substantial loss to follow‐up, some of which was related to death, including drug overdose deaths, while on treatment or before assessment of SVR.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Such groups were excluded from clinical trials of DAA treatment efficacy due to strict eligibility criteria; thus, our cohort represents a real‐world PWID population treated with DAAs. We found that there was no difference in SVR by any of these characteristics, which is similar to the findings from others . However, among PWID who did not achieve SVR, there was a substantial loss to follow‐up, some of which was related to death, including drug overdose deaths, while on treatment or before assessment of SVR.…”
Section: Discussionsupporting
confidence: 88%
“…However, among PWID who did not achieve SVR, there was a substantial loss to follow‐up, some of which was related to death, including drug overdose deaths, while on treatment or before assessment of SVR. Loss to follow‐up was higher among male patients, similar to a recent report from Germany on DAA treatment among people on OAT . This highlights two important issues affecting the overall impact of DAAs on health outcomes: loss to follow‐up and high mortality not related to HCV.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Although, it has been shown that IDU and OST could significantly reduce the SVR, in our study these factors were not associated with treatment effectiveness. In a recent study, it has been shown that reinfection rate is higher among recent IDU compared to past IDU .…”
Section: Discussioncontrasting
confidence: 87%